Characterization of the Bali Cattle Production System in the Breeding Area of Nusa Penida Island - Ibrahim Zakialmaas; Widi, Tri Satya Mastuti; Tristianto Nugroho; Diyan Eka Hantari; Rena Ari Archi Feny (Jurnal Sain Peternakan Indonesia, 2026)
Bali cattle play an important role in Indonesia’s livestock sector, especially among smallholder farmers in remote areas. On Nusa Penida Island, cattle farming faces unique challenges, including limited land, seasonal feed shortages, and restricted access to education and resources. This study aims to characterize the Bali cattle production system in Nusa Penida by examining the relationships between farming resources, management practices, and production outcomes. Data were collected through semi-structured interviews, direct observations, and focus group discussions with 51 smallholder farmers across ten municipalities. Descriptive statistics were used to assess the characteristics of farmers and farm cha. The results show that Bali cattle farmers on Nusa Penida Island are mostly in the early elder phase, with a medium level of education, who use cattle breeding as a source of income. Farms operate small herds of adult cattle under intensive housing systems and rely heavily on family labor. Traditional breeding and feeding practices dominate, shaped by resource constraints and environmental conditions. This study characterizes the current Bali cattle production system on Nusa Penida Island. It highlights the need for improvements in feed management, farmer education from the new generation, and cooperative support to enhance the sustainability and resilience of Bali cattle farming on the island.